Experience and Perception of Online Education among Nursing Faculties during Covid-19 Pandemic in Nepal: A Qualitative Study - Sah, Bimala Kumari; Adhikari, Bibhav; Pandey, Apsara; Karki, Sita; Silwal, Suvekshya (Tribhuvan University Journal, 2023)
Corona virus disease - 2019 (COVID-19), the global pandemic, had jeopardized the educational institutes across the world during 2020 and 2021. The designing, preparedness and effectiveness of e-learning in nursing area were not clearly understood, particularly in a country like Nepal. Thus, the study aimed to explore experiences and perception of online education among nursing faculties during COVID-19 pandemic in Nepal. A Qualitative research design adopted where 15 nursing faculties from different University across the Nepal involved in online classes since 6 months were interviewed based on principles of data saturation using convenience sampling. Ethical approval was obtained from Nepal Health Research Council (NHRC). Written Informed consent was obtained from nursing faculties via email and in-depth interview was carried out. Confidentiality was maintained throughout the study by coding participants’ records. For the data analysis, the thematic analysis and content analysis were done for the faculties’ experiences and perception. Regarding nursing faculties’ experiences and perception on online education, despite the challenges like: technological, environmental, clinical skills and evaluation methods constraints, they had positive enthusiasm like: economical and easy, technological opportunities and competency. It was concluded online class is one of the crucial modes of teaching and learning in difficult circumstances during this pandemic of corona.